2012
DOI: 10.1167/iovs.11-9165
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Expression in Peripheral Blood Monocytes from Patients with Neovascular Age-Related Macular Degeneration

Abstract: PURPOSE. Chemokine signaling and monocytes/macrophages were implicated in the pathogenesis of AMD. We tested the association between chemokines involved in monocyte recruitment and AMD. METHODS.Immunophenotyping for white blood cell (WBC) populations including CD14þþCD16-and CD14þCD16þ monocytes, CD19þ, CD3þ, and CD16þ lymphocytes, and chemokine receptors CCR1, CCR2, CCR5, CX 3 CR1, and CXCR4 was performed on peripheral blood from treatment-naïve neovascular AMD (NV-AMD) patients and controls. The mRNA level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 75 publications
(70 reference statements)
6
57
2
Order By: Relevance
“…Many studies in animal models have established causal links between retinal damage and proinflammatory pathways [20][21][22]. In humans, many studies have shown that AMD patients presented higher expression of proinflammatory cytokines and altered phenotype and functions of immune cells [16,23,24]. This study demonstrated that AMD patients also presented an imbalance in the composition of CD4 + T …”
Section: Discussionmentioning
confidence: 60%
“…Many studies in animal models have established causal links between retinal damage and proinflammatory pathways [20][21][22]. In humans, many studies have shown that AMD patients presented higher expression of proinflammatory cytokines and altered phenotype and functions of immune cells [16,23,24]. This study demonstrated that AMD patients also presented an imbalance in the composition of CD4 + T …”
Section: Discussionmentioning
confidence: 60%
“…These chemokines are involved in leukocyte recruitment, and some have been implicated in AMD previously. The intraocular concentration of CCL2 was elevated in wet AMD eyes [32] and in urine from wet AMD patients [34] but there was no significant difference in serum from wet AMD cases compared to controls [35].…”
Section: Cytokinesmentioning
confidence: 88%
“…CXCL10 was localised to the choroid in AMD eyes, and significantly elevated CXCL10 concentrations measured in serum from AMD patients of all stages, relative to controls [33]. However, no such difference was observed in a study using a similar number of CNV cases (18) and controls (18) [35]. Larger sample sizes are required to validate CXCL10 as a biomarker for AMD.…”
Section: Cytokinesmentioning
confidence: 95%
“…Mononuclear phagocytes including macrophages and microglia have been implicated in the pathogenesis of age-related macular degeneration (AMD) and other retinal degenerative diseases [1,2,3,4,5,6,7,8,9,10,11,12,13]. While multiple evidence supports such an involvement, macrophages and microglia may possibly have both beneficial and deleterious effects in the context of these diseases [1,14].…”
Section: Introductionmentioning
confidence: 99%